Advances towards the development of a cloud-resolving model in South Africa - Bopape, Mary-Jane M.; Engelbrecht, Francois A.; Randall, David A.; Landman, Willem A. (South African Journal of Science, 2014)
Recent advances in supercomputing have made feasible the numerical integration of high-resolution cloud-resolving models (CRMs). CRMs are being used increasingly for high-resolution operational numerical weather prediction and for research purposes. We report on the development of a new CRM in South Africa. Two bulk microphysics parameterisation schemes were introduced to a dynamical core of a two-dimensional Non-hydrostatic σ-coordinate Model (NSM) developed in South Africa. The resulting CRM was used to simulate two 12-day periods and an 8-day period observed during the Tropical Oceans Global Atmosphere Coupled Ocean-Atmosphere Response Experiment. The response of the NSM to the large-scale forcing which occurred over the three periods, and which included both suppressed and active convection, was examined. The NSM is shown to be able to capture the differences in the three experiments and responds correctly to the large-scale forcing (i.e. it is able to distinguish between suppressed and active regimes). However, the model simulations are cooler and drier than the observations. We demonstrate progress made in the development of a CRM in South Africa, which can be used to study the attributes of convective rainfall over the region.